Implementasi Pembelajaran di Jurusan Teknik Geologi dalam Menunjang Program Sustainable Development di Universitas Gadjah Mada - Wawan Budianta; Arifudin Arifudin (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2016)
Environmental Geology and Geology of Mineral Resources were as compulsory subjects in Department of Geological Engineering, Universitas Gadjah Mada, which known as subject dealing with nature system or sustainable development concept. Tese subjects dealing with management of geological resources and minimize of environmental impact of mineral extraction activity. Formerly, the subjects were given to the student by giving traditionally lecture in class only. In this project, this subjects were enhanced by conducted feld visit in order to improve student and lecturer knowledge. Te location for feld visit were waste disposal site in Piyungan area, Yogyakarta continue with Bojonegoro, East Java which traditional mining of oil was located. Te visit was ended for visiting Tawangmangu area, Karanganyar District, Central Java. In this location, the area was vulnerable with landslide hazard. Te tentative conclusion can be drawn from this project was Environmental Geology and Geology of Mineral Resources can be enhanced by conducting of feld visit and the fnal grade of these subjects can be obtained by adding feld visit as additional value.